Why are laterals less affected than main axes by homogeneous unfavourable physical conditions? A model-based hypothesis - Thaler Philippe; Pages Loi c (Plant and Soil, 1999)
When plants develop in strong soils, growth of the root system is generally depressed. However, branching and elongation of branches are often less affected than growth of the main axes, whenever the whole root system encounters even-impeded conditions. On the basis of a model simulating root growth and architecture as related to assimilate availability, we propose a simple hypothesis to explain such behaviour. In the model, growth of each root depends on its own elongation potential, which is estimated by its apical diameter. The potential elongation rate-apical diameter relationship is the same for all the roots of the system and is described by a monomolecular function. Our hypothesis is that the effect of soil strength can be stimulated by introducing an impedance factor in the definition of root maximum potential elongation rate, common to the whole root system. When such impedance factor is applied, it affects more the potential of larger roots(main axes) than that of thinner roots (secondary and tertialry branches). Simulations provided in high impedance conditions led to root systems characterised by short taproots, whereas growth of secondary roots was unaffected and growth of tertiary roots was enhanced. Actual branching density was also higher, although branching rules have been unchanged. Such simulated systems where similar to that observed in strong soils. Friction laws or pore size can be involved in the larger reduction of the potential growth of main axes. Moreover, when growth of main axes is restricted, assimilate availability becomes higher for branches and that could explain that their growth could be increased in a homogeneous strong soil.
Keywords: Carbon allocation; Hevea brasiliensis; Root growth; Root system architecture; Simulation model; Soil impedance